Improving Women Entrepreneurs in Small and Medium Enterprises in Malaysia: Policy Recommendations - Teoh, Wendy Ming Yen; Chong, Siong Choy (2008)
SME has been recognised as a major source of global economic growth and employment and women entrepreneurs have been acknowledged to play critical roles for bringing their ideas and capabilities towards successful achievement of the SME development in their countries. Prior literature indicated that capital, networks affiliation, education, training and counselling, and usage of ICT are important factors influencing the growth of women entrepreneurs in Malaysia. This paper not only helps the government to appropriately identify the appropriate tat-gel of women entrepreneurs, but also leads the Malaysian women entrepreneurs in developing sound skills and capabilities in doing businesses especially at the start-up phase, which might help them to create and sustain successful business ventures.